Analisis Pengendalian Kualitas Produk Kanopi di Bengkel Las Purnama Karya - Ari Septian Cahyadi; Deny Andesta (Jurnal Serambi Engineering, 2022)
The Purnama Karya weld workshop is individual business engaged in the welding industry that produces one of the products, namely the canopy. In the process of canopy production, there is no possibility if there are no results of products that have bad quality. This research uses Failure Mode and Effects Analysis method. The method contains steps for the identification failure mode against product or process by scoring each form of failure mode based on occurrence values, severity values and detection values. The purpose of this research is found out factors that cause canopy product defects, identify the types of potential defects that occur and identify the impacts that occur. The results show that there are defects that occur with the classification of 2 types of defects, welding and painting, where the most common types of defects are welding defects with a frequency of damage of 56.8% and there are also 16 causes of canopy product defects with details of 8 factors that cause weld defects and 8 factors that cause painting defects. The results of the provision of severity, occurrence, and detection are taken in the order of the 3 highest rankings taken from the results of RPN values.